The Influence of the School Environment and Physical Activity on Students Solidarity from a Social Ecology Perspective in Physical Education - Budianto; Muhammad Rehan Fias Hasanuddin; Muh. Adnan Hudain; Muhammad Ishak; Alimin Alwi (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of the school environment and physical activity on student solidarity from the perspective of social ecology in physical education at SDN Karya Baru. The focus of the research is to understand how the conditions of the school environment and students’ involvement in physical activities shape social behavior and solidarity among elementary school students. The study employs a descriptive qualitative approach with 12 informants consisting of students, a physical education teacher, and homeroom teachers. Data collection techniques include in-depth interviews, participatory observation, and documentation. Data analysis follows the stages of data reduction, data presentation, and conclusion drawing/verification. The results show that (1) a supportive school environment plays an important role in fostering social solidarity; (2) physical activity serves as an effective medium for developing cooperation and empathy; (3) the social ecology perspective explains the reciprocal relationship between the environment and students’ solidarity behavior; and (4) teachers and school culture are key factors in internalizing values of togetherness. In conclusion, physical education not only functions to develop physical aspects but also serves as an essential medium for shaping students’ social character and solidarity.